SIMBOLIK PESAN IKLAN KAMPANYE PILPRES 2024 VERSI “OKE GAS PRABOWO GIBRAN PALING PAS" - Fitiryani, Nurul (Sintesa, 2024)
This research highlights how creativity and innovation play an important role in the transformation of the media industry. In general elections, competing for votes is something that political parties usually do. To seek public sympathy, one way is by placing advertisements in the mass media, where they hope that these advertisements can influence the public to choose a political party or leader. who advertises. The aim of this research is to identify and analyze the political messages of Prabowo Gibran's advertisements, so the researchers formulated research with the symbolic title of the 2024 Presidential Election Campaign Advertisement Message "Okay Gas Prabowo Gibran is the Most Fit" on YouTube Richard Jersey. Researchers used qualitative research methods and in this research used semiotic theory by Charles Sanders Pierce. The results of this research state that political advertisements in the campaign carried out by Presidential Candidate Prabowo and Gibran used various signs such as words, symbols, images and colors to convey political messages to voters. In order to influence voters' perceptions and attitudes towards the two candidates, these signs were carefully selected. The conclusion of the political advertisement for the Presidential and Vice Presidential Candidate Prabowo Gibran version of "Prabowo Gibran is the Most Fit" in the 2024 presidential election campaign, there is an effort to build a specialty and uniqueness of this couple, namely that the campaign team has a communication strategy that focuses on creating a positive image of the couple Prabowo and Gibran through advertisements using songs. The combination of Prabowo's political experience and Gibran's descendants is a privilege that creates leadership synergy which is expected to have a positive impact on society. Keywords: Political Messages, Semiotics, Campaigns, Presidential Elections